LIFE FORMS OF COCCINELLIDS DISTRIBUTED IN THE FERGANA VALLEY (Scientific journal of the Fergana State University, 2025)
This article provides information about the life forms and moisture-related groups of coccinellids distributed in the Fergana Valley, as well as their distribution in various biotopes. According to the distribution of coccinellids among phytobionts, it was determined that the coccinellids in the Fergana Valley belong to five main groups: 8 species (22.8%) are herbivores, 9 species (25.7%) are dendrobionts, 9 species (25.7%) are dendroherbivores, 4 species (11%) are dendrotamnobionts, and 5 species (14%) are dendro-tamnobionts. Additionally, in relation to humidity conditions, the coccinellids in the study area were classified into the following ecological groups: mesophiles, mesoxerophiles, and xerophiles. Among the 35 species of coccinellids found in the Fergana Valley, 25 species belong to the mesophilic group, accounting for 71.4%, 7 species belong to the mesoxerophilic group, accounting for 20%, and 2 species belong to the xerophilic group, accounting for 0.2%. The article also presents data on the distribution of coccinellids in various biotopes, including cotton, alfalfa, vegetable-cereal, maize, wild cereal plants, as well as fruit and ornamental tree biotopes.